Prototype Sistem Stock Barang Dengan Metode Economic Order Quantity (EOQ) - Rudi Budi Agung; Suhadi Suhadi; Fauziah Mutiara Ramadhan (Politeknik Harapan Bersama, 2020)
Many stores still use the traditional way of managing their inventory. From taking notes to using Microsoft Excel. Problems will arise when you want to see the existing stock, the best-selling items and which items have to come out first. So that sometimes they have difficulty in getting information on the stock of goods provided that are not in accordance with existing availability. In this study the author uses the Economic Order Quantity method. The Economic Order Quantity method is a management function in inventory. Where goods must be provided in large quantities because they are sold out is one of the advantages of this method. The results of the analysis of this study are the Design and Build of a Stock of Goods System with a web-based Economic Order Quantity method to make it easier for shop owners to collect inventory data, increase economic value and improve service to customers with always available stock.Keywords: Stock of goods, Economic Order Quantity, Web, Microsoft Excel.